Efficiency measurement for hierarchical network systems using network DEA and intuitionistic fuzzy ANP - Serkani, E Shariatmadari; Lotfi, F Hosseinzadeh; Najafi, E; Namin, M Ahadzadeh (Scientia Iranica, 2022)
Regarding the high importance of university in the growth and development of a country, the efficiency of educational and research groups in universities is a vital consideration. The black box Data Envelopment Analysis (DEA) model is mathematical programming for measuring the relative efficiency of a set of Decision-Making Units (DMUs) without considering the operations of the component processes that may have misleading results. To overcome this problem, network models are recommended. This paper intends to propose a hybrid Intuitionistic Fuzzy Analytic Network Process (IFANP) and Network DEA (NDEA) technique to evaluate the efficiency of the Faculty of Basic Sciences of Islamic Azad University. IFANP was used to evaluate the overall weights among all the criteria and sub-criteria and the weights were in turn used in the NDEA model to measure the relative efficiency. A hypothetical example showed that the efficiency of all DMUs was equal to 1 by using the DEA and there was no ranking among the DMUs. The results of the IFANP-NDEA could be more meaningful with full ranking of the DMUs considering the component process operations. Finally, the model could prioritize the efficient DMUs and determine the efficiencies of the DMUs' functions. This model enables managers to identify the areas of weakness in the subject under their study.